Organic waste amendment effects on soil microbial activity in a corn-rye rotation: Application of a new approach to community-level physiological profiling - Garland, J. L. (2010)
Organic fertilizers provide long-term benefits to agronomic soils, but sometimes cause short-term reductions in crop yield due to microbially mediated nitrogen (N) immobilization. A simple, rapid method to assess the integrated use of both, carbon (C) and N by soil microbial communities will be a useful monitoring tool in production agriculture. The present study evaluated a new platform for performing community-level physiological profiles (CLPP) using fluorescent-based detection of O2 consumption by soil slurries within microtiter plates. Response of a spodic Florida soil to 3 organic fertilizer amendment treatments; (1) control with no organic amendment, (2) pelletized class A?A municipal biosolids amendment, and (3) fresh dairy waste solids amendment was measured in soils taken from a corn?rye crop rotation. The CLPP assay was used to assess endogenous and substrate induced (∼75 μg C as acetate, casein, coumaric acid, mannose, or asparagine g−1 soil) respiration, with and without assay N additions (8 μg N-NH4 g−1 soil). Endogenous and substrate-induced respiration were generally greater in the dairy waste-amended soils, as quantified by a reduced lag period and greater response peak. Stimulatory effects from biosolid-amended soils were less extensive and consistent. The degree of N limitation on microbial activity was determined by comparing the response peak with and without N amendment. This difference in response (Ndiff) was greatest for all treatments during the rye exponential growth phase (prior to heading), when extractable soil NH4-N and NO3-N concentrations were lowest (i.e., < 10 mg kg−1). The dairy waste treated soils had greater Ndiff values during the rye crop as compared to the other treatments, particularly for endogenous respiration and mannose-induced respiration. Ndiff was low in all treatments during the corn crop, where extractable soil NH4-N + NO3-N remained at or above 20 mg N kg−1. Plant yield data coincided with our estimates of N-limited microbial activity, with less mid-season rye biomass under dairy waste and no yield response with corn. Overall, these data indicate that this new method allows for a rapid, ecologically relevant evaluation of organic amendment impacts on microbial soil respiration and thereby plant yield response. Further characterization and interpretation of the variation in microbial respiration among specific C substrates and the relative impact of N amendments (i.e., Ndiff), will provide insight to C and N cycling in soils receiving organic N inputs.